Food freedom forever : letting go of bad habits, guilt, and anxiety around food - Hartwig, Melissa (Houghton Mifflin Harcourt, 2016)
Shares advice on how to improve energy and health while letting go of negative food habits, outlining a three-part plan for long-term control and recovery from restriction breaks taken during the holidays, vacations, and times of stress.